An Islamic Analysis of Beijing Declaration on Women Rights in some Selected Local Government Areas of Yobe State - ماداكي، عائشة آدم (جامعة عمار ثليجي الأغواط - معهد علوم وتقنيات النشاطات البدنية والرياضية, 2022)
This Research investigates an Islamic Analysis of the Beijing Declaration on Women Rights in some selected Local Government Areas of Yobe State, Nigeria. It ponders on the history of women rights, concept and its roles in political, social, Economic and religious aspect in Yobe State. Analytical research methodology has been used in preparing this paper. Findings have shown that, Beijing Declaration on Women rights in some selected local Government Areas in Yobe State has not reached most of the women especially in the rural areas, because their rights are more of western than Islamic. Also Women are empowered with many rights and protections under Islamic law and honoured with a dignified stature in the society Parents as well. Finally, this paper recommended that, husbands and Muslim communities should provide sound Islamic Education to their women at home before being exposed to secular education, also Islamic scholars should diversify their knowledge and learn more about western propaganda in order to expose its evil intentions.
Keywords: حقوق المرأة -- الحكومات المحلية -- الشريعة الإسلامية -- نيجيريا